Hidden nature : wild southern caves - Taylor, Michael Ray, 1959- (Vanderbilt University Press, 2020)
"More than 10,000 known caves lie beneath the state of Tennessee according to the Tennessee Cave Survey, a nonprofit organization that catalogs and maps them. In this book, Taylor tells the story of this vast underground wilderness. In addition to describing the sheer physical majesty of the region's wild caverns and the concurrent joys and dangers of exploring them, he examines their rich natural history and scientific import, their relationship to clean water and a healthy surface environment, and their uncertain future"--